Pengujian Subtitusi CaCO3 Taiwan dengan CaCO3 Produk Lokal untuk Industri Berbahan Baku PVC - Anwar Sukito Ardjo; Rofarsyam Rofarsyam (Teknoin, 2005)
The paper reports an experiment to produce  polyvinyl chloride (PVC) using local (from Gunung Kidul) and imported (from Taiwan) CaCO3. The laboratory test shows that PVC produced using Taiwanese CaCO3 is superior over that using local CaCO3 in terms of its flexibity.  Hence, it is not recommended to use local CaCO3 producing PVC-based products that requires high flexibility such as water pipe, cable isolator. On the other hand, the local PVC may be used to produce, for instance,  blinds and compressor.  Keywords: PVC, local CaCO3  , imported CaCO3